KOMBINASI PEMBERIAN TERAPI RELAKSASI BENSON DAN BITTER ORANGE AROMATERAPI TERHADAP PERUBAHAN INTENSITAS NYERI PADA IBU POST SEKSIO SESAREA - DWI - YANTI; Dewi Rosaria Amalia (Akademi Keperawatan Dharma Husada Kediri, 2020)
Introduction: Incidence of Caesarean section showed an increase in various hospitals. In general, cesarean section surgery can cause abdominal pain on the client. Cesarean section labor can cause a higher pain around 27.3% than the normal labor assistance which is only around 9%. Pain management in post-cesarean women used pharmacological and non-pharmacological therapy, One of the non-pharmacological therapies is the combination of Benson relaxation technique and bitter orange aromatherapy to post Caesarean mothers. The purpose of this research was to measure the effectiveness of the Benson relaxation therapy and bitter orange aromatherapy in reducing the intensity of post-cesarean maternal pain. Method: Research design used an experimental design with two measurements of 60 post-cesarean women (30 treated mothers and 30 untreated mothers) in Kertosono Regional Hospital of Nganjuk Regency. The research instrument to measure pain intensity using the pain questionnaire sheet included the Visual Analog Scale (VAS), and the results of pain intensity measurements were documented on the observation sheet and then analyzed using the Mann Whitney U test. Result: The results showed a p-value of 0.005 with α (0.05). Therefore it concluded than administration of combined Benson relaxation therapy and bitter orange aromatherapy can decrease the pain intensity in post-cesarean mothers. Discussion: For further research it is hoped that giving additional non-pharmacological therapies is more beneficial in reducing the intensity of pain in post-cesarean mothers.